Bacillus thuringiensis and Chlorantraniliprole Trigger the Expression of Detoxification-Related Genes in the Larval Midgut of Plutella xylostella - Shabbir, Muhammad Zeeshan; Yang, Xiangbing; Batool, Raufa; Yin, Fei; Kendra, Paul E.; Li, Zhen-Yu (Frontiers in Physiology, 2021)
Background: Diamondback moth (DBM), Plutella xylostella (L.), has developed resistance to many insecticides. The molecular mechanism of DBM resistance to Bt-G033A combined with chlorantraniliprole (CL) remains undefined. Methods: In this study, field-resistant strains of Plutella xylostella to three pesticides, namely, Bacillus thuringiensis (Bt) toxin (Bt-G033A), CL, and a mixture of Bt + CL, were selected to evaluate the resistance level. Additionally, transcriptomic profiles of a susceptible (SS-DBM), field-resistant (FOH-DBM), Bt-resistant (Bt-DBM), CL-resistant (CL-DBM), and Bt + CL-resistant (BtC-DBM) strains were performed by comparative analysis to identify genes responsible for detoxification. Results: The Bt-G033A was the most toxic chemical to all the DBM strains among the three insecticides. The comparative analysis identified 25,518 differentially expressed genes (DEGs) between pairs/combinations of strains. DEGs were enriched in pathways related to metabolic and catalytic activity and ABC transporter in resistant strains. In total, 17 metabolic resistance-related candidate genes were identified in resistance to Bt-G033A, CL, and Bt + CL by co-expression network analysis. Within candidate genes, the majority was upregulated in key genes including cytochrome P450, glutathione S-transferase (GST), carboxylesterase, and acetylcholinesterase in CL- and BtC-resistant strains. Furthermore, aminopeptidase N (APN), alkaline phosphatase (ALP), cadherin, trypsin, and ABC transporter genes were eminent as Bt-resistance-related genes. Expression patterns of key genes by the quantitative real-time PCR (qRT-PCR) proved the credibility of transcriptome data and suggest their association in the detoxification process. Conclusion: To date, this study is the most comprehensive research presenting functional transcriptome analysis of DBM using Bt-G033A and CL combined insecticidal activity.